Psycho-emotional conditions in primary care physicians who serve in a direct vicinity to the frontline - Larysa Kupriianova; Daryna Kupriianova (Journal of Education, Health and Sport)
Introduction. Armed conflicts, wars, social/economic/political/national/racial conflicts and rebellions have been accompanying all periods of the historical development of the mankind. Within the framework of the above-mentioned crises from the point of view of existentialism and the development of the community of events, each person was assigned a certain unique role that was associated with equally unique physical and psycho-emotional consequences. However, even in the XXI century, history, philosophy, medical and political sciences, potentially try to equate the psycho-emotional spectrum of experience that combatants, medical workers, and representatives of the civilian population take on. The Russian Federation's full-scale war against Ukraine shook the continent and became, undoubtedly, an unprecedented trigger for revising the above concept. Thus, based on the fundamental philosophical theory of utilitarianism, as the clue of formation of the palette of human actions, compared with the vision of leading scientists about the specifics of post-demobilization and reintegration processes, as well as those that ensure the social inclusion of ex-combatants, the civilian population and, in particular, medical specialists, who work directly on the front line and, ultimately, completing with the actual scientific and practical experience of a global cohort of medical scientists, who since 2019 have emphasized the relevance of highlighting the different spectrum and specifics of the development of psycho-emotional conditions specifically in front-line medical workers in the framework of a critical existential situation; all this leads to the need to separate representatives of the health care sector into an independent category of active persons within the ongoing wartime, not only from the point of view of the role they play at the front, but also from the point of view of unique psycho-emotional conditions experienced by them under the prism of the profession/role they perform.